Orbital Lymphoma Mimicking Lacrimal Gland Pleomorphic Adenoma - Diego Strianese; Andrea Elefante; Francesco Matarazzo; Angela Panico; Mariantonia Ferrara; Fausto Tranfa (Case Reports in Ophthalmology, 2013)
Purpose: To describe the case of a patient affected by orbital lymphoma mimicking pleomorphic adenoma of the lacrimal gland. Methods: This was a retrospective case report. Results: We present the case of a patient with 15-year history of slowly progressive left proptosis and inferomedial bulbar dislocation who had the presumptive diagnosis of lacrimal gland pleomorphic adenoma based on clinical and radiological features. The patient underwent lateral orbitotomy and lacrimal gland excision. Postoperative histological features were consistent with low-grade B-cell non-Hodgkin lymphoma. Conclusion: The accepted clinico-radiological criteria used for the diagnosis of lacrimal gland fossa lesions might have a certain false-positive rate, even in recent years. The initial surgical approach with the appropriate choice between fine-needle aspiration biopsies, intraoperative biopsies and lacrimal gland excisions might be a challenge.